2002
DOI: 10.3346/jkms.2002.17.6.765
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 beta Induces MUC2 Gene Expression and Mucin Secretion via Activation of PKC-MEK/ERK,and PI3K in Human Airway Epithelial Cells

Abstract: Interleukin 1beta(IL-1beta), a proinflammatory cytokine, is related with inflammatory diseases and it up-regulates MUC2 gene expression and mucin secretion. This study was designed to investigate the signal transduction pathway of the IL-1beta-mediated MUC2 gene expression and mucin secretion in human airway epithelial cells. In cultured human airway NCI-H292 epithelial cells, the steady state of the mRNA level of MUC2 gene expression and mucin secretion induced by IL-1beta were determined by reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 27 publications
1
37
1
Order By: Relevance
“…Another report revealed that IL-1β's stimulation of MUC2 occurs through the protein kinase C (PKC) and ERK pathways (49). In addition, this report also revealed that phosphoinositol 3-kinase (PI3K) inhibitors could partly block the induction of MUC2 without affecting ERK phosphorylation (49). This finding suggests that IL-1β's effect occurs through a parallel PI3K/AKT pathway (49).…”
Section: Muc2 Expression Regulated By Inflammatory Cytokinesmentioning
confidence: 52%
See 2 more Smart Citations
“…Another report revealed that IL-1β's stimulation of MUC2 occurs through the protein kinase C (PKC) and ERK pathways (49). In addition, this report also revealed that phosphoinositol 3-kinase (PI3K) inhibitors could partly block the induction of MUC2 without affecting ERK phosphorylation (49). This finding suggests that IL-1β's effect occurs through a parallel PI3K/AKT pathway (49).…”
Section: Muc2 Expression Regulated By Inflammatory Cytokinesmentioning
confidence: 52%
“…In addition, this report also revealed that phosphoinositol 3-kinase (PI3K) inhibitors could partly block the induction of MUC2 without affecting ERK phosphorylation (49). This finding suggests that IL-1β's effect occurs through a parallel PI3K/AKT pathway (49). IL-4 can induce MUC2 expression in NCI-H292 cells as well as in colon cell lines (50,51).…”
Section: Muc2 Expression Regulated By Inflammatory Cytokinesmentioning
confidence: 72%
See 1 more Smart Citation
“…IL-1b alone and in combination with LPS, can induce the overexpression of mucins in airway epithelial cells, goblet cells and murine biliary epithelial cells (Kim et al, 2002;Levine et al, 1995;Li et al, 1998;Dohrman et al, 1998;Zen et al, 2002;Perdomo et al, 1994;Zychlinsky et al, 1994;Raqib et al, 1995). S. dysenteriae infection causes a severe inflammation in the colon, which is triggered by extensive production of proinflammatory cytokines such as tumor necrosis factor alpha (TNFa) and IL-1b, which have been found in the stool and plasma of patients with acute shigellosis (Perdomo et al, 1994;Zychlinsky et al, 1994;Raqib et al, 1995;Kim et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the MUC2 gene in NCI-H292 human airway epithelial cells is mediated by interleukin-1b (IL-1b) through the activation of protein kinases PKC, MEK, ERK and PI3K (Kim et al, 2000;Kim et al, 2002;Perrais et al, 2002). IL-4 induces gene expression of MUC5AC and MUC4 in goblet cell metaplasia in vitro and in vivo (Temann et al, 1997;Dabbagh et al, 1999;Damera et al, 2006).…”
Section: Introductionmentioning
confidence: 99%